Short report: The potential of PCR on skin flakes from bed linens for diagnosis of scabies in an outbreak. - Raïssa Tjon-Kon-Fat; Laurène Peckeu; Susan Hahné; Eric de Coster; Wendy Tas; Bas Wintermans; Anneke Bergmans; Mariska Petrignani; Ewout Fanoy (PLoS Neglected Tropical Diseases, 2021)
Background Scabies outbreaks are common in nursing homes in the Netherlands. In October 2018, a local public health service (PHS) in The Hague was notified of a new scabies outbreak in a nursing home in that region. The PHS initiated an outbreak investigation. Cases were defined as: possible (reported symptoms), probable (scabies-like lesions) and confirmed (PCR or microscopy in skin flakes). Head-to-toe examinations were performed of all residents and those staff members who reported symptoms suggestive of scabies. Skin scrapings of lesions were tested either with microscopy or by PCR. Experimentally for case finding, skin flakes from bed linens of residents who reported symptoms of itchiness but did not have primary lesions were sent for PCR testing. Principal findings All residents (41) and 37/44 staff were included in this outbreak investigation. We identified 30 possible, four probable and six confirmed cases. The overall attack rate for probable/confirmed cases was 10/78 (13%). Of the six confirmed cases, two were confirmed by PCR, three by microscopy, and one showed positive findings with both techniques. Two out of the three bed-linen specimens were PCR-positive. Conclusions In this outbreak of scabies in a nursing home, PCR was used on skin flakes from bed linens, which led to the detection of two additional cases. This illustrates the potential of PCR during the investigation of scabies outbreaks.